The Effects of a New Peerage. - Woodward, G. M. (George Moutard), ca. 1760-1809 ?; Cruikshank, Isaac, 1756?-1811? ? (Fores, S. W., 1797)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Aristocracy (Social class) -- Great Britain